PENDIDIKAN NILAI MENUJU KEBEBASAN MANUSIA DALAM ALAM DEMOKRASI - Purwosaputro, Supriyono (DIMENSI PENDIDIKAN, 2005)
Value clarification only reflects and implicates in the gathering condition where all the people are able to develop the value of respectness, solidarity and interiority. Value clarification in the learning process that support the value which is found in human beingâs life including value of freedom. The point of value is the way of thinking, the way of attitudes, and the way of behaviour, either personal or together. Value clarification will make the students become more mature in finding and giving the positive value in their freedom Progressivism philosophy is relevant to develop the value of clarification to the freedom of human being in democration. Since there is an opinion of basic progressivism a value has a quality of social, besides progresivism giving pressure to the freedom of the students, progressivism also cares to the disipline of the students so that they get advantages. Progressivism as the philisophy of education will get big problems in managing an education in a managed curriculum Keyword : value clarification, freedom, democracy, progresivism